If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12x + -1 = -8x + 11 Reorder the terms: -1 + -12x = -8x + 11 Reorder the terms: -1 + -12x = 11 + -8x Solving -1 + -12x = 11 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. -1 + -12x + 8x = 11 + -8x + 8x Combine like terms: -12x + 8x = -4x -1 + -4x = 11 + -8x + 8x Combine like terms: -8x + 8x = 0 -1 + -4x = 11 + 0 -1 + -4x = 11 Add '1' to each side of the equation. -1 + 1 + -4x = 11 + 1 Combine like terms: -1 + 1 = 0 0 + -4x = 11 + 1 -4x = 11 + 1 Combine like terms: 11 + 1 = 12 -4x = 12 Divide each side by '-4'. x = -3 Simplifying x = -3
| 3x=-1+19 | | 0=-3x^2+6x+7 | | -8q+6+5q-3= | | 4z=12-48 | | y=-3x^2+6x+7 | | 2x+4=8x+4 | | 3x^2+36x+108=0 | | 7t=3t-16 | | 6n-9=21 | | -21w+5+3w-1= | | 0=4y-4 | | (X-15)-(10-2x)=1 | | -20=4y-4 | | 5x+2-7=5x+3 | | 5X+4-6X=11 | | -40=4y-4 | | 180=x+50+4x+25 | | (X-15)-(2x-10)=1 | | .5-10d=1 | | 6y-3=12 | | -4x-(x-9)=8 | | .6(2h-4)=2.4+1.2h | | 9x+10=6x+55 | | 5x+2-7+5x=-8x+4 | | 6y-0=12 | | 6m^2-13m-15=0 | | -12+5g+8-g= | | 6y-(-3)=12 | | -3.2-x=-19.14 | | 15x^2-25x-10= | | 5x+2-8+2x=6x+4 | | 21x+13x+14x-8=180 |